Isochronal annealing study of Mg-implanted p-type GaN activated by ultra-high-pressure annealing. (16th April 2021) - Hirukawa, Kazufumi; Sumida, Kensuke; Sakurai, Hideki; Fujikura, Hajime; Horita, Masahiro; Otoki, Yohei; Sierakowski, Kacper; Bockowski, Michal; Kachi, Tetsu; Suda, Jun
Abstract: Isochronal annealing was performed on Mg-ion-implanted GaN under 1 GPa N2 ambient pressure for 5 min at temperatures of 1573–1753 K. Secondary ion mass spectrometry showed diffusion of Mg atoms and introduction of H atoms during annealing. Deeper diffusion was observed with increasing temperature. From Hall-effect measurements, p-type conductivity was found even for the sample with the lowest annealing temperature of 1573 K. For this sample, the acceptor activation ratio was 23% and the compensation ratio was 93%. The acceptor activation ratio increased to almost 100% and the compensation ratio decreased to 12% with increasing annealing temperature.